FEATURES OF THE PROCESS OF TRAINING YOUNG PLAYERS IN BEGINNER TRAINING GROUPS - Muminov Feruz Ilxomovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. Football is taught in institutions of additional education in children's and youth sports schools (youth sports schools). For admission to the Youth School, parents of future students provide a written application, a birth certificate and, without fail, a certificate of the child's health status. After that, the children take exams in physical and special training, that is, they are diagnosed when they enroll in the Youth School.